Clinicopathological Study of Skin Adnexal Tumours at Tertiary Care Centre - Dr. Chandrashekhar P. Bhale; Dr. Riya Shah, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Skin, which is composed of epidermis, dermis and skin adnexa has high incidence of Skin tumours. Subgroups of skin adnexal neoplasms are distinguished based on the differentiation of these tumours towards sebaceous, apocrine, eccrine, and hair follicles. Though clinical features provide clues to the diagnosis, histopathology remains the gold standard in the confirmation of the diagnosis. Categorization of the tumor as benign or malignant is vital for therapeutic and prognostic purposes. Present study was conducted to assess frequency, histological subtype, benign or malignant nature and age distribution of skin adnexal tumours which will further help diagnosis towards their line of differentiation. Materials and Methods: Present study is a cross sectional observation study conducted from October 2022 to September 2024. 43 cases of skin adnexal tumors of all ages & both gender who has been advised histopathology were enrolled. After Histo-morphological analysis of the tumors they were classified according to predominant pattern of differentiation into follicular, sebaceous, eccrine, and apocrine. Statistical analysis was performed using SPSS software, version 20. Observations and Results: majority cases i.e. 17 (39 %) were from age group between 41 to 60 years. Males were 24 (56 %) and females were 19 (44 %). In majority i.e. 28 (65 %) Head, neck & face was involved. Benign cases were 40 (94 %) whereas Malignant were 3 (6 %). In 26 (61 %) cases Hair follicle was involved. In 4 (10 %) Sebaceous gland, in 6 (13 %) Apocrine gland and in 7 (16 %) Eccrine gland was involved. amongst Benign cases Trichelemmal cyst was the commonest found in 12 (29 %) cases. Conclusion: To conclude Majority of the skin adnexal tumours were benign compared to malignant. Head, neck and face region were found as the commonest site of involvement and maximum cases involved hair follicle